Comparison of the mucosal and systemic antibody responses in Covid-19 recovered patients with one dose of mRNA vaccine and unexposed subjects with three doses of mRNA vaccines - Liu, Shaojun; Tsun, Joseph G. S.; Fung, Genevieve P. G.; Lui, Grace C. Y.; Chan, Kathy Y. Y.; Chan, Paul K. S.; Chan, Renee W. Y. (Frontiers in Immunology, 2023)
Background: Immunity acquired from natural SARS-CoV-2 infection and vaccine wanes overtime. This longitudinal prospective study compared the effect of a booster vaccine (BNT162b2) in inducing the mucosal (nasal) and serological antibody between Covid-19 recovered patients and healthy unexposed subjects with two dose of mRNA vaccine (vaccine-only group). Method: Eleven recovered patients and eleven gender-and-age matched unexposed subjects who had mRNA vaccines were recruited. The SARS-CoV-2 spike 1 (S1) protein specific IgA, IgG and the ACE2 binding inhibition to the ancestral SARS-CoV-2 and omicron (BA.1) variant receptor binding domain were measured in their nasal epithelial lining fluid and plasma. Result: In the recovered group, the booster expanded the nasal IgA dominancy inherited from natural infection to IgA and IgG. They also had a higher S1-specific nasal and plasma IgA and IgG levels with a better inhibition against the omicron BA.1 variant and ancestral SARS-CoV-2 when compared with vaccine-only subjects. The nasal S1-specific IgA induced by natural infection lasted longer than those induced by vaccines while the plasma antibodies of both groups maintained at a high level for at least 21 weeks after booster. Conclusion: The booster benefited all subjects to obtain neutralizing antibody (NAb) against omicron BA.1 variant in plasma while only the Covid-19 recovered subjects had an extra enrichment in nasal NAb against Omicron BA.1 variant.